Assistance for 3R (Reduce, Reuse, Recycle) based waste management in Desa Wisata Selasari - Fransdito Ali Ilyas; Adil Ridlo Fadillah; Tedi Rustendi; Abdul Azis Ramadhan; Hadiyan Prayoga (Jurnal Abmas, 2025)
Selasari Village, as a leading tourist destination, faces crucial challenges, including a surge in seasonal waste volume that is not optimally managed due to limited infrastructure and limited public understanding of the 3R principles: Reduce, Reuse, and Recycle. This community service program aims to enhance community capacity, initiate source separation practices, and develop Standard Operating Procedures (SOP) adaptable to fluctuations in visitor numbers. Using a participatory approach that includes socialization, training in appropriate technologies such as composting and ecobricks, and intensive mentoring, this program actively engages tourism managers and local communities. The intervention results demonstrate a significant increase in partner awareness and participation, evidenced by the implementation of waste sorting, the revitalization of the "Saling Peduli" Waste Bank activities as an economic incentive base, and the production of value-added materials. Furthermore, this program produced outputs in the form of formatted SOP documents and visual educational waste bin facilities. However, operational effectiveness during peak visitation periods remains constrained by logistical limitations; thus, this study concludes that integrating surge capacity protocols and strengthening partnerships with recycled markets are necessary. These recommendations are crucial to ensuring the sustainability of waste management, which must be both technically sound and adaptive to tourism dynamics.   Abstrak Desa Selasari, sebagai destinasi wisata unggulan, menghadapi tantangan krusial berupa lonjakan volume sampah musiman yang belum terkelola optimal akibat keterbatasan infrastruktur dan minimnya pemahaman masyarakat mengenai prinsip 3R yang terdiri dari Reduce, Reuse, Recycle. Program pengabdian ini bertujuan meningkatkan kapasitas masyarakat, menginisiasi praktik pemilahan sampah di sumber, serta menyusun Standar Operasional Prosedur (SOP) yang adaptif terhadap fluktuasi pengunjung. Melalui metode partisipatif yang mencakup sosialisasi, pelatihan teknologi tepat guna seperti komposting dan ecobrick, serta pendampingan intensif, program ini melibatkan pengelola wisata dan komunitas lokal secara aktif. Hasil intervensi menunjukkan peningkatan signifikan dalam kesadaran dan partisipasi mitra, dibuktikan dengan implementasi pemilahan sampah, revitalisasi aktivitas Bank Sampah “Saling Peduli” sebagai basis insentif ekonomi, serta produksi material bernilai tambah. Selain itu, program ini menghasilkan luaran berupa dokumen SOP terformat dan fasilitas tempat sampah edukatif visual. Kendati demikian, efektivitas operasional pada masa puncak kunjungan masih menghadapi kendala logistik, sehingga studi ini menyimpulkan perlunya integrasi protokol kesiapsiagaan (surge capacity) dan penguatan kemitraan pasar daur ulang. Rekomendasi ini krusial untuk menjamin keberlanjutan pengelolaan sampah yang tidak hanya teknis tetapi juga adaptif terhadap dinamika pariwisata. Kata Kunci: 3R; desa wisata; partisipasi masyarakat; pengelolaan sampah